Analysis of Cognitive Aspects of Test Techniques in Islamic education Learning - Winda Sulistyarini; Maemonah (Tarbiyah Departement collaboration with AMCA, 2022)
Assessment activities in schools are part of the learning process to reflect an understanding of individual students and measure progress. In assessment, the domain is the cognitive aspect and is part of the assessment of intellectual abilities related to the student's knowledge. This study aimed to identify and analyze assessments of cognitive aspects of testing techniques in PAI learning at SMP Negeri 2 Nusawungu. This research uses field research, interview techniques, and documentation. The findings of this study suggest that PAI teachers' assessments of cognitive aspects of testing techniques tend to use objective testing techniques, such as short-answer and oral, and subjective forms of descriptive testing techniques. The cognitive level of the test technique is C1-C2, and the dimensions are factual knowledge and conceptual knowledge. This testing technique has advantages and disadvantages. The advantage is that there is an increase in the learning outcomes of class VIII students, which are known to be better than the previous semester. Meanwhile, the drawback is that the test technique has not yet reached the HOTS level and uses only a few types of instrument techniques.